Cali families with international migrants: before and after - Micolta León, Amparo; Escobar Serrano, María Cénide (Sociedad y Economía, 2010)
The purpose of this article is to analyze some aspects that denote the economic conditions of homes with immigrant fathers and/or mothers in Spain and the related changes that have derived from the remittances sent to the families that remain in Colombia. At the moment of leaving, the immigrant as well as their family builds hopes around these remittances. However, the remittances have not been able to completely satisfy the expectations that they had before the trip. The households, from which the information presented here has been obtained, show that their economic situation has not changed substantially. Furthermore, there are conflicts because of the amount, reception, and handling of the remittances.